Knowledge, Prevention Practice and Associated Factors of Stroke Among Hypertensive and Diabetic Patients – A Systematic Review - Melak AD; Wondimsigegn D; Kifle ZD (Dove Medical Press, 2021)
Abreham Degu Melak,1 Dawit Wondimsigegn,2 Zemene Demelash Kifle1 1University of Gondar, College of Medicine and Health Science, School of Pharmacy, Department of Pharmacology, Gondar, Ethiopia; 2University of Gondar, College of Medicine and Health Science, School of Pharmacy, Department of Pharmaceutics and Social Pharmacy, Gondar, EthiopiaCorrespondence: Abreham Degu MelakUniversity of Gondar, College of Medicine and Health Science, School of Pharmacy, Department of Pharmacology, Gondar, EthiopiaEmail abrishdegu8@gmail.comIntroduction: Because of the inadequate level of public awareness of the disease, the incidence of stroke has been sharply rising. Eventually, due to the prehospital delay, many stroke cases could not be eligible for thrombolysis thereby poor rehabilitative outcome has been tremendously increased. Thus, this study aimed to review the level of knowledge, prevention practice, and associated factors of stroke among hypertensive and diabetic patients.Methods: A systematic review of primarily published articles (2010- 2020) related to knowledge and prevention practices of stroke was performed by searching online electronic databases like PubMed, Google Scholar, Refseek, Science direct, ResearchGate, and manual Google search by using the keywords and MeSH terms. Studies conducted on knowledge and prevention practices amongst hypertensive and/or diabetic patients were included.Results: Out of 531 searched studies, 42 articles were identified to be reviewed. The reported overall knowledge of stroke was ranging from 4.4% to 79%. Knowledge to the signs/symptoms of stroke was 23.6% to 87%. However, 15% to 77% of subjects were also reported that they did not know any sign of stroke. The range of risk factor knowledge was 10.5% to 86.6%. The reported level of stroke prevention practice was 2.4% to 72% but physical activity and weight reduction practice were relatively low. Inadequate level of knowledge and prevention practice of stroke was related to elderly, female gender, uneducated, unmarried, rural residents, economically low, comorbidity and unemployed individuals.Conclusion: The current finding revealed that the level of knowledge and prevention practice of stroke was inadequate. Hence, the finding highlights health educational programs should be planned as an important avenue to enhance stroke awareness among the high-risk populations.Keywords: stroke, knowledge, warning sign, risk factor, prevention